Analisis Pemahaman Karyawan Bank Syariah terhadap Product Knowledge Tabungan Wadiah dalam Perspektif Perilaku Organisasi - Sugeng Nugroho (Pusat Studi Ekonomi Islam Sekolah Tinggi Ekonomi Islam Hamfara, 2018)
Employees (people) are one important element in the company, including banks. Because employees with a good product konowledge will increase the professionalism of the company. The purpose of this study was to determine the understanding of employees of Bank Muamalat Yogyakarta Branch of Wadiah savings products from the perspective of organizational behavior. This type of research is field research with a quantitative descriptive research framework. Using probability stratified sampling technique. The data collection method uses a questionnaire with a sample size of 55 respondents. Analysis of perception test data using Chi-Square, processed using SPSS 25.0. The results found: the level of employee understanding of Wadiah savings products is on a scale of understanding and understanding.